The study of language - Yule, George 1947- (Cambridge University Press, 2023)
This bestselling textbook provides an engaging and user-friendly introduction to the study of language. Assuming no prior knowledge of the subject, Yule presents information in bite-sized sections, clearly explaining the major concepts in linguistics through all the key elements of language. This eighth edition has been revised and updated throughout, with major changes in the chapters of origins, phonetics, syntax, semantics, pragmatics, discourse analysis, first and second language acquisition, and culture. There are 40 new study questions and over 60 new and updated additions to the Further Readings. To increase student engagement and to foster problem-solving and critical thinking skills, the book includes over 20 new tasks. An expanded and revised website provides students with further resources, including a substantial study guide. This is the most fundamental and easy-to-use introduction to the study of language